Characteristics of rod regeneration in a novel zebrafish retinal degeneration model using N-methyl-N-nitrosourea (MNU) - Tappeiner, C; Balmer, J; Iglicki, M; Schuerch, K; Jazwinska, A; Enzmann, V; Tschopp, M (Public Library of Science, 2013)
Primary loss of photoreceptors caused by diseases such as retinitis pigmentosa is one of the main causes of blindness worldwide. To study such diseases, rodent models of N-methyl-N-nitrosourea (MNU)-induced retinal degeneration are widely used. As zebrafish (Danio rerio) are a popular model system for visual research that offers persistent retinal neurogenesis throughout the lifetime and retinal regeneration after severe damage, we have established a novel MNU-induced model in this species. Histology with staining for apoptosis (TUNEL), proliferation (PCNA), activated Müller glial cells (GFAP), rods (rhodopsin) and cones (zpr-1) were performed. A characteristic sequence of retinal changes was found. First, apoptosis of rod photoreceptors occurred 3 days after MNU treatment and resulted in a loss of rod cells. Consequently, proliferation started in the inner nuclear layer (INL) with a maximum at day 8, whereas in the outer nuclear layer (ONL) a maximum was observed at day 15. The proliferation in the ONL persisted to the end of the follow-up (3 months), interestingly, without ongoing rod cell death. We demonstrate that rod degeneration is a sufficient trigger for the induction of Müller glial cell activation, even if only a minimal number of rod cells undergo cell death. In conclusion, the use of MNU is a simple and feasible model for rod photoreceptor degeneration in the zebrafish that offers new insights into rod regeneration.